Philosophical trilogy in critical visual analysis – Case of refugee discourse. (December 2018) - Iftikhar, Waseem
Abstract: Through Critical Visual Analysis (CVA) using the theoretical lens of social semiotics, this paper critically analyzes two images of the Syrian boy who was washed ashore during a refugee journey. The images resulted in a debate and shaped a serious discourse around the Middle Eastern refugee crises. However, the same image from different angle, was used by Daesh/ISIS (in Dabiq Magazine) to present a different kind of 'reality'/ideology, signifying the possibility of depiction of diverging ideologies through identical images. This research adopts a Conceptual Analytical Approach blending the work of three of the 18th and 19th Century philosophers through their ideas of Genius, Fine Art, Tragedy and Pessimism. To this end, considering Kant, Schopenhauer and Nietzsche's philosophy of arts, this paper critically analyses the images in an effort to reinforce the significance of philosophical analysis in CVA, through deconstruction. In doing so, the article embraces a Logical Analytical Approach, overlaying these selected concepts on contemporary issue within broader refugee discourse. Integrating the contemporary social semiotic concepts with philosophical concepts signifies the need for such Integrative Analytical Approach.